Myths associated with the use of modern contraceptive methods in multigestational contraceptives in a peruvian health post, 2023 - Alcántara-Auqui, María Ysabel (2023)
Objective: To identify myths regarding the use of contraceptive methods. Material and methods: This research was carried out in the Collanac Health Post and is qualitative, observational, descriptive, cross-sectional and exploratory. The selection of the sample will be by convenience and will be applied to 10 pregnant women who have 4 or more pregnancies and who live at least 3 months in the jurisdiction, who have not used contraceptive methods for at least 6 months before the current pregnancy, and who have not planned the current pregnancy. Results: Hormonal Contraceptive Methods: Patients report symptoms such as headache, infertility, amenorrhea, weight gain, and they also report that they had heard from family members that these methods made them fat and produced infertility, all of which causes them to abandon modern contraceptive methods and leads to unwanted pregnancies. Barrier Contraceptive Methods: most know and have used condoms, but many refer their husbands do not wish to continue because they did not like using condoms. Copper T: Patients mentioned that it is a cause of uterine cancer and hemorrhage as well, in turn that if there was failure with the copper t the child would be born with the copper t. Tubal ligation: Many of the women interviewed did not have much information about this method and some said that women who have tubal ligation do not live long. Conclusions: There are myths that influence the use of contraceptive methods.